Reformar el artículo 188 del código del trabajo con relación al despido intempestivo en el que se reincorpore el derecho al reintegro del trabajador. - Bravo Rodríguez, Tatiana Alexandra (2014)
This thesis is entitled: "REFORM THE ARTICLE 188 OF THE CODE OF WORK REGARDING THE ACCIDENTAL DISCHARGE IN WHICH THE RIGHT TO REFUND reinstated WORKER" In our country despite our current "Constitution of the Republic of Ecuador" passed by referendum by the Ecuadorian people and published in Official Gazette No. 449, dated October 20, 2008, it has important safeguards for the rights of workers, in the eighth section Labour and social Security, in Article 33, states: "Work is a right and a social duty, and an economic, source of personal fulfillment and economic base. The State shall ensure that persons working full respect for their dignity, decent living wages and fair remuneration and performance of a safe work freely chosen or accepted "; Establishing the economic and social relevance of the right to work within a framework of dignity, freedom and equality for workers, also found in the provisions in Article 325 states: "The State shall guarantee the right to work. All modes working as employees or self, including self-support tasks and human care are recognized; as productive and social actors, to all workers and employees”"; and in Article 326 establishes the principles governing labor relations in the country, such as the dignity of wages, job security, promotion of full employment, the right to associate, prevention of occupational risks and social security rights ; even workers' rights is violated by the high rate of sudden layoffs made employers. The unfair dismissal is an illegal form of termination of employment, mainly because no just cause of the employer, it can only terminate the employment relationship through the grounds specified in article 169 of the Labour Code, mainly with Eviction and legal mechanisms Views Well before the labor inspectorate of the territorial constituency. Current regulations of the said body of laws, has some shortcomings that do not guarantee the rights of workers, especially job security, because once the employer has engaged in unfair dismissal, after a long and tedious process, and if tested of course, is required to compensate with X insignificant, same values that do not solve the problem of unemployment in which the worker is, becoming a social problem both personally and in the family, these aspects do not only have to do with economics, but even psychological. The theoretical, legal and doctrinal collection, case studies, conducting surveys and interviews allowed me to get recognized criteria very clear and precise foundations of literature, which contributed to the verification of the objectives and the recruitment of the hypothesis ; both the Constitution of the Republic of Ecuador, as the Labour Code. It is thus that the present research work, in the final part contains a proposal for Legal Reform, which includes the legal means to significantly reduce the rate of sudden layoffs in Ecuador. For all these reasons I believe that it is important to do this legal research to establish the need to reform the Labour Code to allow the Act has the protective nature of the worker's rights, stability and continuity of work through labor reinstatement in cases of dismissal without any legal procedure or process.